Bahasa Inggris - Mela Rosita; Herly Evanuarini; Agus Susilo; Premy Puspitawati Rahayu; Ita Wahju Nursita (Jurnal Penelitian Pendidikan IPA, 2026)
The development of functional meat products has gained increasing attention, particularly through the incorporation of dietary fibers to enhance nutritional value while maintaining product quality. This study aimed to evaluate the effect of adding 3% banana blossom flour (BBF) on the quality characteristics of spent hen meat sausages subjected to refrigeration at a temperature of 4°C over periods of 0, 7, 14, and 21 days. The experiment was arranged in a completely randomized design, with storage duration as the treatment factor and five replications. The parameters observed included moisture content, pH, texture, color (L, a*, b*), microbial counts, peroxide value, and sensory attributes during cold storage. The results showed that storage periods of spent hen meat sausages with BBF addition exerted a statistically significant effect (P < 0.01) on all parameters. During storage, pH value, redness, yellowness, total microorganism, and peroxide value increased, whereas moisture content, lightness, and sensory quality decreased. In conclusion, BBF addition extended the shelf life of sausages, allowing to remain acceptable until 21 days of cold storage, despite a gradual decline in sensory quality associated with increased peroxide values. Moreover, the utilization of BBF facilitates the enhancement of agricultural by-products as part of sustainable food innovation.